(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
Sumartini.2019.Improving the Ability to Read English Through the Application of the Scramble Technique in Class IX Students of SMP Negeri 8 Penajam Paser Utar. This Research is aimed improving the ability to read English through the application of the technique of scramble (playing while learning) in students of class VIII SMP N 6 Satengk Malengke. This research is a class action research or often called classroom action research. Classroom action research is research that aims to provide improvements in student learning processes. This research will be carried out in Class IXSMP Negeri 8 Penajam Paser Utara. The research is planned to be in the even semester of the 2019/2020 academic year for 3 months. The subjects of this study were students in Class IXSMP Negeri 8 Penajam Paser Utara, in the academic year 2019/2020 as many as 25 students, 13 male students and 12 female students. Based on the related results show that: (1) Scramble technique in English subjects in Class IX students of SMP Negeri 8 Penajam Paser Utara have been implemented well. In cycle I the value of completeness Student Learning Outcomes is 56 or included in the criteria Less and increased in the second cycle to 88% percentage of completeness Student Learning Outcomes on or included in the criteria very well so that it can be concluded that learning to read comprehension using Scrambel techniques can improve reading skills understanding of grade IX students of SMP Panajem Paser Utara.